Kupfer- und Eisenoxide als Konversions-Elektrodenmaterialien für Lithium-Ionen-Batterien: Thermodynamische und Elektrochemische Untersuchungen - Lepple, Maren (Schriftenreihe des Instituts für Angewandte Materialien, Karlsruher Institut für Technologie, 2016)
Conversion-type electrodes are promising electrode materials for future lithium ion batteries since they exhibit high specific capacities compared to intercalation-type eclectrodes. In this work, a thermodynamic approach was used to elucidate the electrochemical behavior of conversion-type electrodes using Li-Cu-O and Li-Fe-O as model material systems. electrochemical properties can be calculated using self-sonstistent thermodynamic descriptions developed in this work.